Factors affecting financial literacy among secondary school students in Selangor / Aida Hazlin Ismail, Ridhuan Mat Dangi and Shukriah Saad - Ismail, Aida Hazlin; Mat Dangi, Ridhuan; Saad, Shukriah (Faculty of Accountancy, 2019)
The purpose of this study is to explore the factors that may influence the financial literacy of the secondary school’s students in Selangor. This study is to increase understanding about the role of parents, peers and society on financial literacy and financial well-being among Malaysian school students. Expanded understanding of financial well-being among the school students will further help them in the processes of managing their own financial management independently. Currently, not many studies in Malaysia that examine the factors that affecting the financial literacy among the secondary school students. Most prior research investigate the factors affecting the college and university students. Based on social cognitive theory, this study investigates the factors that may affect the secondary school students in Selangor. The samples are three boys and three girls from one of the Secondary schools in Puncak Alam. Interviews were conducted on the selected samples and data were transcribe according to thematic format. Results show that factors that may influence the financial literacy of the school students are the social interaction, individual characteristics and environmental factors. Hence, students are able to manage their own money based on the influence of their family members especially their parents and sibling. In addition, environmental factors also place an important role in influencing the financial management and literacy of the students.